Phylogenetic Tree Formation Analysis of SARS-CoV-2 ORF3a Protein using Neighbor-Joining - Mahfudhah, Nariswari; Rodiah, Rodiah; Maukar, Maukar (Green Publisher Indonesia, 2023)
SARS-CoV-2 or coronavirus disease is the cause of the world pandemic in 2019 (Adnan et al., 2020). In its development, SARS-CoV-2 has occurred mutations, resulting in the emergence of several new variants (Hartono and Yusuf, 2021). One of the efforts made to determine the occurrence of mutations is to build and analyze phylogenetic tree (van Dorp et al., 2020). ORF3a protein is one of the constituent genes of the SARS-CoV-2 virus (Ahmad et al., 2022). The dataset was obtained through a database that has been publicly published on the NCBI website (https://www.ncbi.nlm.nih.gov/). The data used are homo sapiens from China (Wu et al., 2020), USA (Daniel et al., 2020), France (Shannon et al., 2020), Indonesia (Rantam et al., 2021), Australia (Caly et al., 2020), and Mexico (Mendoza-Salazar et al., 2022). The phylogenetic tree was constructed using the Neighbor-Joining method. The result is ORF3a from Mexico and France are closely related. ORF3a from Mexico and France have the same level of distance and similarity with ORF3a from China and ORF3a from Indonesia have proximity to ORF3a USA.